تأثیر إضافة الکبریت إلى الخلطة الخرسانیة - nan, nan (Iraqi Journal of Civil Engineering, 2010)
This research includes study of the of effect of adding sulphur, which is obtained from Samrraa factory on the properties of concrete like compressive strength, flexural strength and splitting tensile strength. The concrete mixes were: (1:8.5:8.5:7), (1:8.5:8.5:9), (1:8.5:8.5:12) and (1:1.5:3:0) (cement: sand: gravel: sulphur) respectively. The results refer to increasing of compressive strength , flexural strength and splitting tensile strength with increasing of sulphur ratio but increasing decreased at age (28)day with respect to ordinary concrete (sulphur ratio=0%).